Hereditary Multiple Exostoses—A Review of the Molecular Background, Diagnostics, and Potential Therapeutic Strategies - Bukowska-Olech, Ewelina; Trzebiatowska, Wiktoria; Czech, Wiktor; Drzymała, Olga; Frąk, Piotr; Klarowski, Franciszek; Kłusek, Piotr; Szwajkowska, Anna; Jamsheer, Aleksander (Frontiers in Genetics, 2021)
Hereditary multiple exostoses (HMEs) syndrome, also known as multiple osteochondromas, represents a rare and severe human skeletal disorder. The disease is characterized by multiple benign cartilage-capped bony outgrowths, termed exostoses or osteochondromas, that locate most commonly in the juxta-epiphyseal portions of long bones. Affected individuals usually complain of persistent pain caused by the pressure on neighboring tissues, disturbance of blood circulation, or rarely by spinal cord compression. However, the most severe complication of this condition is malignant transformation into chondrosarcoma, occurring in up to 3.9% of HMEs patients. The disease results mainly from heterozygous loss-of-function alterations in the EXT1 or EXT2 genes, encoding Golgi-associated glycosyltransferases, responsible for heparan sulfate biosynthesis. Some of the patients with HMEs do not carry pathogenic variants in those genes, hence the presence of somatic mutations, deep intronic variants, or another genes/ loci is suggested. This review presents the systematic analysis of current cellular and molecular concepts of HMEs along with clinical characteristics, clinical and molecular diagnostic methods, differential diagnosis, and potential treatment options.